Isolamento, caracterização e análise da multipotência de células-tronco adultas derivadas do tecido adiposo de bovinos e bubalinos - SAMPAIO, Rafael Vilar (Universidade Federal do Pará, 2017)
Adult stem cells are known for their potential and plasticity to differentiate into several different cell types (multipotency), which has implications for cell therapy as well as reproductive biotechnologies. In the present work we report isolation and characterization of mesenchymal stem cells (MSCs) derived from adipose tissue of cattle and buffaloes. Cells isolated by enzymatic digestion of adipose-tissue biopsy were grown for at least ten passages in vitro giving support to of their proliferative capacity. These cells were also subjected to immunophenotypic characterization to visualize the presence, of CD90, CD105 and CD79, and absence, of CD45, CD34 and CD73, wich are positive and negative markers of MSCs, respectively. In order to determine their multipotency, the cells were induced to differentiate into three different cell types and stained with tissue-specific dyes (Chondrogenic-Alcian Blue, Osteogenic- Alizarin Red and Adipogenic-Oil-Red O) to ensure their differentiation into chondrocytes, ostoblasts and adipocytes. Our results indicate that adipose tissue of cattle and buffaloes can be used as a source of mesenchymal stem cells (MSCs), turning them into an interesting option of animal models for cell therapy and regenerative medicine. Additionally, these cells may be relevant for reproductive biotechnology since the use of MSCs as nuclear donors has been linked to an increase in the developmental rates of cloned embryos.